2018
DOI: 10.1108/ijssp-08-2017-0097
|View full text |Cite
|
Sign up to set email alerts
|

Mediating role of organizational commitment in the relationship between human resource management practices and employee engagement

Abstract: Purpose The purpose of this paper is to examine the mediating role of organizational commitment (OC) on the relationship between human resource management (HRM) practices and employee engagement among banking employees in the context of an emerging economy namely Bangladesh. Design/methodology/approach The survey data include 383 employees from 30 private commercial banks in Bangladesh. For analyzing the data, structural equation modeling is employed with the bootstrapping method. Findings This study finds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
83
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(133 citation statements)
references
References 165 publications
(285 reference statements)
12
83
2
Order By: Relevance
“…Findings of this study suggest that training and development is an important antecedent of employee engagement, and a positive relationship exists between both variables (training and development, and employee engagement). These findings are consistent with Aktar and Pangil (2018). Findings of this study suggest that when organizations provide training to help employees perform their job task effectively and also provide development opportunities, employees feel their organization cares about personal development which makes them more engaged with their job and organization.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Findings of this study suggest that training and development is an important antecedent of employee engagement, and a positive relationship exists between both variables (training and development, and employee engagement). These findings are consistent with Aktar and Pangil (2018). Findings of this study suggest that when organizations provide training to help employees perform their job task effectively and also provide development opportunities, employees feel their organization cares about personal development which makes them more engaged with their job and organization.…”
Section: Discussionsupporting
confidence: 87%
“…Findings of this study revealed that a fair rewards system positively influence employee engagement in Saudi Arabia's telecom sector and these findings are consistent with Aktar and Pangil (2018). Findings of this study suggest that a fair rewards system indirectly delivers a message to all employees that rewards will be given on fair bases so that those who have desire to obtain these rewards need to work hard.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…When employees are committed to the survival of the organization, the insertion of the organizational climate becomes a link between the employees and the organization. Mostly, the goals of the organization are echoed by organizational climate, which is beneficial to the employees and assists in the enhancement of commitment among employees in the organization (Aktar & Pangil, 2018). Notably, variables under organizational climate such as leadership, motivation, and decision-making have been found by some studies as predictors International Journal of Human Resource Studies ISSN 2162-3058 2020 of organization commitment (Al-Madi, Assal, Shrafat, & Zeglat, 2017;Warsi, Fatima, & Sahibzada, 2009).…”
Section: Organizational Climate and Organizational Commitmentmentioning
confidence: 99%